2021
DOI: 10.1523/jneurosci.2415-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Occipital Gyrus Is Organized along Common Gradients of Spatial and Face-Part Selectivity

Abstract: Inferior occipital gyrus is organised along common gradients of spatial and face-part selectivityGradients of spatial and face-part selectivity in IOG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Such pattern was also observed in the Control Experiments. We also observed similar spatial patterns between eyes-mouth bias and visual field bias in vertical direction ( Figure 4—figure supplement 1 ), which is consistent with previous findings in inferior occipital gyrus ( de Haas et al, 2021 ). While the right OFA and right pFFA have been considered as sensitive to facial components and whole faces respectively, in our data they showed similar spatial profiles of eyes and mouth responses along the posterior-anterior dimension.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Such pattern was also observed in the Control Experiments. We also observed similar spatial patterns between eyes-mouth bias and visual field bias in vertical direction ( Figure 4—figure supplement 1 ), which is consistent with previous findings in inferior occipital gyrus ( de Haas et al, 2021 ). While the right OFA and right pFFA have been considered as sensitive to facial components and whole faces respectively, in our data they showed similar spatial profiles of eyes and mouth responses along the posterior-anterior dimension.…”
Section: Resultssupporting
confidence: 91%
“…A recent study has revealed that in the inferior occipital gyrus, where the OFA located, both tunings for retinotopic location and face parts ( de Haas et al, 2021 ). Although the tuning peak maps were idiosyncratic across individuals, the two tuning maps were correlated within individuals, suggesting a relationship between face parts configuration and their typical retinotopic configuration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that in the inferior occipital gyrus, where the OFA located, both tunings for retinotopic location and face parts (34). Although the tuning peak maps were idiosyncratic across individuals, the two tuning maps were correlated within individuals, suggesting a relationship between face parts configuration and their typical retinotopic configuration.…”
Section: Discussionmentioning
confidence: 94%
“…The IOG participates in the related processes of visual processing such as correlated gradients of spatial and face-part selectivity due to typical face-directed gaze behavior (De Haas et al, 2021 ). As a simple measurement of connectivity between a single node and all other nodes in networks, the DC represents the importance of a node (Telesford et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NE measures how efficiently information is exchanged over the network (Ottet et al, 2013 ). The decrease of Dc and Ne of the left IOG was positively correlated with the intra-modular interaction of the occipital lobe module and the inter-modular interaction of the parietal occipital module, indicating that the left IOG is a core node for information transmission within the occipital lobe and between the parietal occipital lobe (De Haas et al, 2021 ). In other words, the dysfunction of the left IOG plays an important role in the integration of whole brain function and further affects the connection between the occipital lobe and the parietal lobe.…”
Section: Discussionmentioning
confidence: 99%